School Management in Venezuela - Nacarid Rodriguez; Mildred Meza (Universidad Autónoma de Madrid, 2018)
A description of the school management in Venezuela appears from the perspective that offers the laws, the regulations and other normative documents of this function for the compulsory schooling administered by the Ministry of Education and Sports. We also analize the school management in the recent context of the Venezuelan Educational System. The requirements for the entrance to the directive positions, the conditions of remuneration and the in-service trainning are described. Finally, the main work problems of the principals, their difficulties and contradictions, in a stage of transition derived from the political and constitutional changes from the year of 1999 and its perspective are transformed towards the future immediate.